Internet use during coronavirus disease of 2019 pandemic: Psychiatric history and sociodemographics as predictors - Jovic, Jelena (Indian J Psychiatry, 2020)
Coronavirus disease of 2019 (COVID-19) pandemic and related containment measures have grossly affected the daily living and created a need for alternative ways of social communication and entertainment. The aim of this study was to explore the use of various Internet contents depending on sociodemographics and on psychiatric history of participants. This cross-sectional, population-based study is a part of a wider international multicenter study. A total of 1275 participants across Serbia (71.1% of females; average age = 41.81 ± 12.52 years) were recruited using two-level chain-referral sampling method. The participants filled in an anonymous online questionnaire that included questions on sociodemographic data, psychiatric history, and various aspects of increased Internet use since the pandemic. The data were analyzed using a series of multiple logistic regressions. About two-thirds of the sample reported using Internet more during the pandemic. All of the tested regression models, apart from models predicting browsing religion and travel/tourism, were significant, explaining from about 2% (for the contents specific for COVID-19) up to 34.4% (for the sexual content) of variance of use. Reporting a previously diagnosed psychiatric disorder was a significant predictor of greater Instagram use and browsing sexual and sport-related content since the pandemic. To the best of our knowledge, the study is the first to report on the relationship between Internet using and mental health, during COVID-19 pandemic, in the Balkan region. The findings showed various patterns of the increased use of Internet contents since the pandemic referring to both potentially positive and negative Internet influences.